KASHMIR TOURISM: POSSIBILITIES AND CHALLENGES - Yousuf Rather, Aqib (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Jammu and Kashmir has been a famous tourist destination for decades, making it one of the world's most popular places. As long as there have been lush forests, refreshing springs, beautiful gardens, perennial rivers, spectacular alpine landscapes, and pleasant temperatures, the state of Jammu and Kashmir will continue to be recognised as a famous tourist destination across the globe. Resources have been opened up, both in terms of investment and generation, resulting in job creation and socioeconomic development for the local community; poverty reduction and sustainable development have also been achieved. Jammu and Kashmir's integration with the rest of the globe has been facilitated by tourism. The region's social and economic environment is impacted by the influx of tourists, who number in the millions each year. It is estimated that between 50 and 60 percent of the people in J&K are employed in the state's tourism business in some capacity. The tourist sector contributes around 15% to the state's gross domestic product. In spite of its prominence in the state's economy, substantial attempts have not yet been made to determine the impact of J&K's most important industry. Both real and perceived threats in the local community may be blamed on tourism. Cultural identity may be at risk due to tourism's move toward catering to tourists' expectations and needs, particularly those from local and global markets, according to some experts. In Jammu and Kashmir, concerns have been voiced about the socio-cultural, economic, and environmental consequences of these trends. This study aimed at shedding light on the prospects as well as issues confronting the Jammu and Kashmir tourism industry.